Bone in Anorexia - Miquel, Anne; Bousson, Valérie (Seminars in Musculoskeletal Radiology, 2023)
Anorexia nervosa is a feeding disorder involving intentional weight loss. Restricted dietary intake leads to disturbed bone metabolism due to various factors, notably endocrine, that affect bone microarchitecture and incur risk of fracture. Mild to moderate anorexia shows a paradoxical increase in bone marrow adipose tissue, whereas severe forms show gelatinous transformation known as serous atrophy of bone marrow (SABM). Imaging assessment of the mineralized and adipose components uses several techniques: dual-energy X-ray absorptiometry, computed tomography, chemical shift magnetic resonance imaging (MRI), and single-voxel MR spectroscopy. SABM induces MRI bone signal disturbances that can be hard to interpret and may hinder visualization of the fracture line.
Keywords: anorexia nervosa; marrow adipose tissue; serous atrophy of bone marrow; osteoporosis; stress fracture